IN SEARCH OF THE ORIGINS OF ISRAELITE ANICONISM - S I Kang (Acta Theologica)
For a long time, aniconism has been presented as one of the most distinctive characteristics of the religion of ancient Israel. Aniconism refers to the absence or repudiation of divine images. Such a tradition was inconceivable to Israel’s neighbours, where the care, feeding, and clothing of a deity, represented in the form of a divine statue, played a central role in national cults (Jacobsen 1987:15-32; Berlejung 1997:45-72; Walker & Dick 2001; Roth 1992:113-147; Roth 1993:57-79). The issue of aniconism has, therefore, been the subject of much scholarly debate. In discussing the concept of aniconism, this article follows Mettinger’s (1995:18) distinction between de facto aniconism (the mere absence of iconic representations of a deity) and programmatic aniconism (the repudiation of such representations). Many theories on the origins of the strong aniconic tradition in Yahwism have been put forward. Some major theories will be critically reviewed, and a new synthesis with reference to archaeological and iconographic data will be presented.